FROM HUSSERL TO LEVINAS: THE ROLE OF HYLETIC DATA, AFFECTION, SENSATION AND THE OTHER IN TEMPORALITY. - Poleshchuk, Irina (Problems / Problemos, 2009)
This article discloses the question of the pre-giveness of the other and alterity by analyzing and comparing the temporality of consciousness and the role of affection and sensation in Husserl and Levinas. I argue that within the intentional low of consciousness one can find non-intentional structures, i.e. affection and hyletic data which mark a passivity of consciousness, break intentional act and welcome the other. While discussing the temporal structure of consciousness the special attention is given to the discussion of pra-impression.